2021
DOI: 10.3390/cancers13143497
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Pencil Beam Scanning Proton Therapy in Locally Advanced Non-Small Cell Lung Cancer: Propensity Score Analysis

Abstract: This study compared the efficacy and safety of pencil beam scanning proton therapy (PBSPT) versus intensity-modulated (photon) radiotherapy (IMRT) in patients with stage III non-small cell lung cancer (NSCLC). We retrospectively reviewed 219 patients with stage III NSCLC who received definitive concurrent chemoradiotherapy between November 2016 and December 2018. Twenty-five patients (11.4%) underwent PBSPT (23 with single-field optimization) and 194 patients (88.6%) underwent IMRT. Rates of locoregional contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our previous retrospective study showed that PBT was associated with tendencies of better survival and decreased incidences of severe treatment-related toxicity compared to X-ray RT in patients with IPF, but the differences were not statistically significant because of the limited number of patients [18]. Because of the limited capacity and waiting time for PBT, most patients with locally advanced NSCLC received IMRT in our institution [20]. Patients treated with PBT had worse pulmonary function at baseline compared to those treated with IMRT.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our previous retrospective study showed that PBT was associated with tendencies of better survival and decreased incidences of severe treatment-related toxicity compared to X-ray RT in patients with IPF, but the differences were not statistically significant because of the limited number of patients [18]. Because of the limited capacity and waiting time for PBT, most patients with locally advanced NSCLC received IMRT in our institution [20]. Patients treated with PBT had worse pulmonary function at baseline compared to those treated with IMRT.…”
Section: Introductionmentioning
confidence: 83%
“…Breath-hold or respiratory gating was applied for patients with tumor motion ≥ 1 cm. The prescribed dose was 60 GyE or higher, and dose fractionation was individualized according to the tumor size, location, and stage [20,26]. For peripherally located, small-sized tumors, 60 GyE in 4 fractions was prescribed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation induced lung injury (RILI) after postoperative intensity modulated proton therapy (IMPT) in a patient with stage III locally advanced lung adenocarcinoma: a case report the risk of locoregional recurrence reached as evidently as 20-40% even after complete resection, adjuvant and postoperative chemotherapy (1,2). Postoperative radiation therapy (PORT) improved the locoregional recurrence survival (LRFS) in resected pIIIa-N2 NSCLC (3).…”
Section: Case Reportmentioning
confidence: 99%
“…It has been demonstrated that postoperative chemotherapy can reduce distant metastasis for patients with positive lymph nodes. However, the risk of locoregional recurrence reached as evidently as 20–40% even after complete resection, adjuvant and postoperative chemotherapy ( 1 , 2 ). Postoperative radiation therapy (PORT) improved the locoregional recurrence survival (LRFS) in resected pIIIa-N2 NSCLC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%